Peran Lingkungan Keluarga, Motivasi, dan Pengetahuan Kewirausahaan terhadap Minat Berwirausaha Mahasiswa - Prasiska, Dilla Wahyu; Mariyanti, Eka; Nasrah, Rasidah (CV. ITTC INDONESIA, 2024)
This study aims to investigate the effect of family environment, entrepreneurial motivation, and entrepreneurial knowledge on the entrepreneurial interest of students of the Faculty of Economics and Business (FEB) of XXX University in Padang City. The population used in this study were active students of FEB of XXX University in Padang City in the 2020 and 2021 academic years, totaling 384 people. The non-probability sampling technique was used for sample selection, and sampling was carried out using the Rao soft Sample Size Calculator Software Technique so that a sample of 102 respondents was obtained. The results of research and data analysis show that entrepreneurial motivation is the most influential variable on entrepreneurial interest, with a beta value of 0.496. This indicates that students who have high entrepreneurial motivation tend to have greater entrepreneurial interest. However, family environment and entrepreneurial knowledge also have a significant influence on student entrepreneurial interest, although not as strong as entrepreneurial motivation.